Improving Quran Reading Skills with the Al-Baghdadi Method at the Muhammadiyah Blawong 1 Elementary School Yogyakarta - Santoso, Dimas Urip (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The education system in Indonesia, especially Islamic education, issues a program every semester that must be taken by students, in the research at the elementary school, namely SD Muhammadiyah Blawong | Yogyakarta there is a program to read the Qur'an, then the researcher chose the Al-Baghdadi method by means of recognizing hijaiyah letters, conjunctions and how to recite them. This type of research is carried out by means of